Faktor Faktor Yang Berpengaruh Terhadap Tingkat Resiko Kredit Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2009-2013 - Fayakun, Nuar Nanda, Dr. Syamsudin, MM (2016)
This study aims to: 1) To determine the effect of the Capital Adequacy Ratio (CAR) on the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 2) To determine the effect of the Loan to Deposit Ratio (LDR) to the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 3) To determine the effect of firm size (Size) of the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 4) To determine the effect of Operating Expenses to Operating Income (BOPO) on the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 5) To determine the effect of CAR, LDR, company size and BOPO imultaneously on the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. The hypothesis in this study were: 1) Anticipated Capital Adequacy Ratio (CAR) significantly affects the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 2) Loan to Deposit Ratio (LDR) significantly affects the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 3) The size of the company (Size) significantly affects the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 4) Operating Expenses to Operating Income (BOPO) significantly affects the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. 5) CAR, LDR, company size and BOPO simultaneously significant effect on the level of credit risk in banking companies listed in Indonesia Stock Exchange 2009-2013 period. Data needed in this research is secondary data obtained from the banking company's financial statements obtained from BEI. The amount of data in this study were 140 data. Analysis of the data used in this research is multiple linear regression, t test, F test and coefficient of determination. The results of data analysis in this study can be concluded that: 1) Capital Adequacy Ratio (CAR) significantly affects the level of credit risk (NPL). 2) Loan to Deposit Ratio (LDR) significantly affects the level of credit risk (NPL). 3) The size of the company (Size) significantly affects the level of credit risk (NPL). 4) Operating Expenses to Operating Income (BOPO) had no significant effect on the level of credit risk (NPL). 5) CAR, LDR, company size and BOPO simultaneously significant effect on the level of credit risk (NPL).